Digital transformation in the financial system: A comprehensive review of the literature on fintech and financial inclusion - Winarni, Riani; Akbar, Tri Sanatha Wahyu (Privietlab, 2025)
The digital technology revolution has brought a fundamental paradigm shift in the global financial services ecosystem, creating a digital transformation that integrates financial technology (fintech) as a key catalyst for expanding people's access to finance. Indonesia, the country with the largest digital economy in the ASEAN region, faces challenges as well as great opportunities in the implementation of digital transformation of the financial system, where the level of financial inclusion has reached 85.1%, but digital financial literacy has only reached 48%. This study aims to conduct a comprehensive analysis of digital transformation in the financial system through a systematic literature review that covers fintech developments and their impact on financial inclusion, identifies global and national trends, evaluates the effectiveness of fintech models, and develops a conceptual framework for the development of a sustainable fintech ecosystem. This study uses a qualitative approach with the Systematic Literature Review (SLR) method on national and international journal articles for the period 2021-2025 from Google Scholar, with the inclusion criteria of reputable articles that are relevant to the digital transformation of the financial system and financial technology. The analysis shows that fintech has proven effective in increasing financial inclusion for unbankable and underbanked segments through digital lending, mobile banking, e-wallets, and Sharia fintech. Key success factors include adequate technological infrastructure, digital literacy, consumer trust, supportive regulation, and strategic collaboration. Key challenges include regulatory uncertainty, digital divides, cybersecurity, and financial system stability. Digital transformation of the financial system requires proportionate regulation, massive digital infrastructure investment, sustainable literacy programs, robust security frameworks, and multi-stakeholder collaboration to realize an inclusive and sustainable fintech ecosystem.